1996
DOI: 10.1007/bf01291784
|View full text |Cite
|
Sign up to set email alerts
|

Taurine infused intrastriatally elevates, but intranigrally decreases striatal extracellular dopamine concentration in anaesthetised rats

Abstract: In the present study we infused taurine (50, 150 or 450 mM, 2 microliters/min for 4h) into the dorsal striatum or into the substantia nigra via microdialysis probe and estimated the extracellular concentrations of dopamine and its metabolites, 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), in the dorsal striatum of anaesthetised rats. Intrastriatal infusion of taurine elevated striatal dopamine at all concentrations studied. At the 450 mM concentration taurine elevated the extracellular do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The function of the neurotransmitter implies the existence of specific taurine receptors and the neuromodulator role of interference with the functions of other transmitter systems 80 . Taurine injection within the Substantia nigra reduces extracellular dopamine 81 and modulates striatal dopaminergic transmission 82 , but another study reported that direct injection of taurine into the striatum had significantly increased extracellular dopamine 83 .…”
Section: Discussionmentioning
confidence: 99%
“…The function of the neurotransmitter implies the existence of specific taurine receptors and the neuromodulator role of interference with the functions of other transmitter systems 80 . Taurine injection within the Substantia nigra reduces extracellular dopamine 81 and modulates striatal dopaminergic transmission 82 , but another study reported that direct injection of taurine into the striatum had significantly increased extracellular dopamine 83 .…”
Section: Discussionmentioning
confidence: 99%